DIGITAL CROSSWORD ON 7TH GRADER’S VOCABULARY MASTERY: THE EFFECTIVENESS & STUDENT’S PERCEPTION - Sihombing, Elena Febiola; Utami, IGA Lokita Purnamika; Wahyuni, Luh Gede Eka (Yavana Bhasha : Journal of English Language Education, 2025)
The study aims to investigate the significant difference of students’ vocabulary mastery between those who are taught by using digital crossword and those who are with conventional learning by using small group discussion learning method. This study also explore students' perceptions of using digital crosswords in learning English vocabulary for 7th-grade students at SMP Negeri 1 Singaraja. This research was a sequential explanatory mixed method design. In this study, the sample was divided into two groups, which are an experimental group and the control group. The research instruments used were post-test, questionnaire and interview. The post-test was used to collect students' scores in investigating the significant difference of digital crosswords. Meanwhile, questionnaire and interview were used to obtain students' perceptions of using digital crosswords in learning vocabulary. The questionnaire was designed based on the Technology Acceptance Theory (TAM) by Davis (1989). The results showed that after learning with digital crosswords, there was a significant difference on students' vocabulary mastery. students who were taught by digital crosswords have increased vocabulary mastery more than students who were taught by conventional learning. The result showed positive perceptions of students after using digital crosswords. Students feel interested and actively participate in learning. This study implies that digital crosswords can be used as an effective media to improve students' vocabulary mastery and interest in English.